Commonality Benefit Analysis for Maintenance Technical Publications of Civil Aircraft Based on Learning Effect - Yongjie ZHANG; Yongqi ZENG; Kang CAO; Yuefan JIANG; Ke LIANG (International Journal of Aerospace Engineering)
The maintenance technical publications of civil aircraft are important engineering information for maintaining the continued airworthiness of aircraft, strictly guiding the maintenance of aircraft, and seriously affecting the efficiency of aircraft maintenance. The commonality between maintenance technical publications corresponding to different aircraft types brings primitive experience to aircraft operators for the maintenance of newly introduced types, which can accelerate the adaptation of maintenance personnel and reduce the maintenance time of aircraft. To quantify the commonality of maintenance technical publications, we constructed a commonality evaluation system for maintenance technical publications by combining the Analytic Hierarchy Process and Fuzzy Comprehensive Evaluation Method. Then, a commonality benefit evaluation model of maintenance technical publications is established by analyzing the impact of commonality on the learning effect, which can analyze and calculate the monthly maintenance time savings of newly introduced models after the effects of commonality. The commonality benefit analysis for maintenance technical publications in this paper is mainly for aircraft operators, which can provide the reference for their decision to introduce new aircraft types.